Tolerance and Tachyphylaxis to Head Twitches Induced by the 5-HT2A Agonist 25CN-NBOH in Mice - Buchborn, Tobias; Lyons, Taylor; Knöpfel, Thomas (Frontiers in Pharmacology, 2018)
The serotonin (5-HT) 2A receptor is the primary molecular target of serotonergic hallucinogens, which trigger large-scale perturbations of the cortex. Our understanding of how 5-HT2A activation may cause the effects of hallucinogens has been hampered by the receptor unselectivity of most of the drugs of this class. Here we used 25CN-NBOH (N-(2-hydroxybenzyl)-2,5-dimethoxy-4-cyanophenylethylamine), a newly developed selective 5-HT2A agonist, and tested it with regard to the head-twitch-response (HTR) model of 5-HT2A activity and effects on locomotion. 25CN-NBOH evoked HTRs with an inverted u-shape-like dose-response curve and highest efficacy at 1.5 mg/kg, i.p. HTR occurrence peaked within five minutes after agonist injection, and exponentially decreased to half-maximal frequency at ~11 minutes. Thorough habituation to the experimental procedures (including handling, saline injection, and exposure to the observational boxes one day before the experiment) facilitated the animals’ response to 25CN-NBOH. 25CN-NBOH (1.5 mg/kg, i.p.) induced HTRs were blocked by the 5-HT2A antagonist ketanserin (0.75 mg/kg, 30 min pre), but not by the 5-HT2C antagonist SB-242084 (0.5 mg/kg, i.p., 30 min pre). SB-242084 instead slightly increased the number of HTRs occurring at a 3.0-mg/kg dose of the agonist. Apart from HTR induction, 25CN-NBOH also modestly increased locomotor activity of the mice. Repeated once-per-day injections (1.5 mg/kg, i.p.) led to reduced occurrence of 25CN-NBOH induced HTRs. This intermediate tolerance was augmented when a second (higher) dose of the drug (3.0 mg/kg) was interspersed. Short-interval tolerance (i.e., tachyphylaxis) was observed when the drug was injected twice at intervals of 1.0 and 1.5 hours at either dose tested (1.5 mg/kg and 0.75 mg/kg, respectively). Inducing ketanserin-sensitive HTRs, which are dependent on environmental valences and which show signs of tachyphylaxis and tolerance, 25CN-NBOH shares striking features common to serotonergic hallucinogens. Given its distinct in vitro selectivity for 5-HT2A over non5-HT2 receptors and its behavioral kinetics, 25CN-NBOH appears to be a powerful tool for dissection of receptor-specific cortical circuit dynamics, including 5-HT2A related psychoactivity.